Dynamic structure of active nematic shells - Rui Zhang (Nature Portfolio, 2016)
In active matter, chemical energy is transformed into mechanical motion; theoretical descriptions of nematic liquids are useful in understanding such phenomena. Here, Zhang et al. model the dynamics of active nematic liquid crystals confined onto a spherical shell in systems that mimic cell motion.